Human talent management in the work performance of a marketing company - Peru - Chuquitucto Cotrina, Lisseth Katherine; Marín Terrones, Luz Elena; Mostacero Arévalo, Nataly Francesca; Otiniano León, Mabel Ysabel; Alburuqueque Arana, Fausta Elizabeth (LACCEI, 2023)
The purpose of the research was to learn about human talent management and its influence on work performance in a marketing company in Peru. The type of research was basic, with a quantitative approach and the research design was non-experimental. It is worth mentioning that the unit of analysis was duly represented by each employee of the marketing company in Peru, therefore, with respect to the size of the population there were 30 employees, who were taken as part of the sample after having applied inclusion and exclusion criteria. On the other hand, the variables were operationalized through the dimensions proposed, the survey was used as a data collection technique and the questionnaire was used as an instrument (through Google Forms) consisting of 27 items, with answers whose values comprised a scale of 1 - 5, the same that were understood by the members of the sample allowing a quick filling of their answers. On the other hand, we worked on the presentation of results, using descriptive and inferential statistics. As part of the descriptive results, we have the management of human talent with 70% that was placed at a high level, the data showed that leadership, capacity, identity and work environment are maintained at a considerable level; on the other hand, the employees of the trading company in Peru with 80%, expressed that job performance is located at a high level, where productivity and commitment maintain a considerable level, however, a small percentage shows the existence of the lack of commitment that exists in the trading company by the employees. Finally, the SPSS program was used to process the data, using Spearman's Rho correlation test, resulting in a high positive Spearman's relationship (r=0.815) between the study variables (GTH and DL) in a marketing company in Peru, with a significance value (p=0.000) of less than 5%, which means that we accept the research hypothesis that Human Talent Management does influence labor performance in a marketing company - Peru.